Fine Mapping of Lycopene Content and Flesh Color Related Gene and Development of Molecular Marker–Assisted Selection for Flesh Color in Watermelon (Citrullus lanatus) - Wang, Chaonan; Qiao, Aohan; Fang, Xufeng; Sun, Lei; Gao, Peng; Davis, Angela R.; Liu, Shi; Luan, Feishi (Frontiers in Plant Science, 2019)
Lycopene content and flesh color are important traits determined by a network of carotenoid metabolic pathways in watermelon. Based on our previous study of genetic inheritance and initial mapping using a F2 populations of LSW-177 (red flesh) × Cream of Saskatchewan (pale yellow flesh), red flesh color was controlled by one recessive gene regulating red and pale yellow pigmentation, and a candidate region related to lycopene content was detected spanning a 392,077 bp region on chromosome 4. To obtain a more precise result for further study, three genetic populations and a natural panel of 81 watermelon accessions with different flesh colors were used in this research. Herein, we narrowed the preliminary mapping region to 41,233 bp with the linkage map generated from F2 populations of LSW-177 (red flesh) × Cream of Saskatchewan (pale yellow flesh) with 1,202 individuals. Two candidate genes, Cla005011 and Cla005012, were found in the fine mapping region, therein Cla005011 was a key locus annotated as a lycopene β-cyclase gene. Phylogenetic tree analysis showed that Cla005011 was the closest relative a gene in gourd. LSW-177 × PI 186490 (white flesh) and another BC1 population derived from Garden Female (red flesh) × PI 186490 were generated to verify the accuracy of the red flesh candidate gene region. By analyzing the expression levels of candidate genes in different developmental stages of different color watermelon varieties, Cla005011 for the expression differences were not the main reason for the flesh color variation between COS and LSW-177. This indicated that the LCYB gene might regulate fruit color changes at the protein level. A new marker-assisted selection system to identify red and yellow flesh colors in watermelon was developed with flesh-color-specific CAPS markers and tested in 81 watermelon accessions.